Heat kernel coefficients for massive gravity - Ferrero, Renata; Fröb, Markus B.; Lima, William C.C. (Journal of Mathematical Physics, 2024)
We compute the heat kernel coefficients that are needed for the regularization and renormalization of massive gravity. Starting from the Stueckelberg action for massive gravity, we determine the propagators of the different fields (massive tensor, vector and scalar) in a general linear covariant gauge depending on four free gauge parameters. We then compute the non-minimal heat kernel coefficients for all the components of the scalar, vector and tensor sector, and employ these coefficients to regularize the propagators of all the different fields of massive gravity. We also study the massless limit and discuss the appearance of the van Dam–Veltman–Zakharov discontinuity. In the course of the computation, we derive new identities relating the heat kernel coefficients of different field sectors, both massive and massless.<br
Keywords: Cosmological constant; Gravitation; Gravitons; Auxiliary field; Heat kernel approach; Renormalization and regularization; Gauge fixing